2020
DOI: 10.1371/journal.pone.0233260
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair deficiency in metastatic prostate cancer: Response to PD-1 blockade and standard therapies

Abstract: BackgroundWhile response rates to anti-PD1 therapy are low in unselected metastatic castration resistant prostate cancer (mCRPC) patients, those with inactivating mutations in mismatch repair (MMR) genes (i.e. MMR deficiency; MMRd) or microsatellite instability (MSI) are thought likely to respond favorably. To date, there is limited published data on this biologically distinct and clinically relevant subgroup's natural history and response to treatment. MethodsWe retrospectively identified patients at two acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 27 publications
2
70
0
Order By: Relevance
“…Radiographic responses occurred in 4 out of these 6 patients, and 5 patients were still on therapy for as long as 89 weeks [ 83 ]. Graham et al recently reported that of a total of 17 patients with dMMR and/or MSI-H mPC who received pembrolizumab, 53% had a ≥ 50% PSA reduction, and 87.5% of them remained on treatment at a median follow-up of 12 months [ 84 ]. Taking into account the above findings, microsatellite testing should be undertaken and pembrolizumab considered for patients with MSI-H status.…”
Section: Main Textmentioning
confidence: 99%
“…Radiographic responses occurred in 4 out of these 6 patients, and 5 patients were still on therapy for as long as 89 weeks [ 83 ]. Graham et al recently reported that of a total of 17 patients with dMMR and/or MSI-H mPC who received pembrolizumab, 53% had a ≥ 50% PSA reduction, and 87.5% of them remained on treatment at a median follow-up of 12 months [ 84 ]. Taking into account the above findings, microsatellite testing should be undertaken and pembrolizumab considered for patients with MSI-H status.…”
Section: Main Textmentioning
confidence: 99%
“…5,6 Individuals with a germline pathogenic variant in the MSH2, MLH1, MSH6, PMS2 or EPCAM genes (ie, Lynch syndrome) have tumors that are deficient in mismatch repair, and these tumors are responsive to inhibitors of the programmed death 1 (PD1) pathway. 7,8 In addition to changing treatment decisions, identifying pathogenic germline variants can have health, reproductive, and psychosocial implications for the patient and the patient's family members. 9,10 A pathogenic germline variant can imply disease risk for both the patient and his or her relatives.…”
Section: The Intersection Of Precision Oncology and Germline Geneticsmentioning
confidence: 99%
“…Considering their advanced stage, they respond relatively well to androgenic deprivation, but less so to taxanes once castration-resistant. Afflicted patients are a subgroup currently considered candidates and evaluated for anti-PD1 or anti-CTL4 immunotherapy [26,27]. On the germinal level, Pritchard et al [15] reported that, of 692 patients with mPCa, 12% showed deleterious germline mutations (1% involving MSH2, 1% MSH6 and 2% PMS2).…”
Section: Germline Mutations Driving Pcamentioning
confidence: 99%